Social determinants of health and local government: understanding and uptake of ideas in two Australian states - Angela Lawless; Anna Lane; Felicity‐ann Lewis; Fran Baum; Patrick Harris (Elsevier, 2017)
Abstract Objective: To examine the awareness and perceptions of local government staff about the social determinants of health (SDoH) and health inequity and use of these ideas to shape policy and practice. Methods: 96 staff at 17 councils in South Australia or New South Wales responded to questions in a pilot online survey concerning: sources of knowledge about, familiarity with the evidence on, attitudes towards, and uses of ideas about the social determinants of health. Eight of 68 SA councils and 16 of 152 NSW councils were randomly selected stratified by state and metropolitan status. Differences between states and metropolitan/non‐metropolitan status were explored. Results: The majority of respondents (88.4%) reported some familiarity with ideas about the broad determinants of health and 90% agreed that the impact of policy action on health determinants should be considered in all major government policy and planning initiatives. Research articles, government/professional reports, and professional contacts were rated as important sources of knowledge about the social determinants of health. Conclusion: Resources need to be dedicated to systematic research on practical implementation of interventions on social determinants of health inequities and towards providing staff with more practical information about interventions and tools to evaluate those interventions. Implications: The findings suggest there is support for action addressing the social determinants of health in local government. The findings extend similar research regarding SDoH and government in NZ and Canada to Australian local government.